PENGARUH SUPERVISI KEPALA SEKOLAH TERHADAP MOTIVASI KERJA DAN KINERJA GURU SMP DI KECAMATAN PESISIR KABUPATEN SIAK - DEWI MASTURA; GIMIN GIMIN; DUDUNG BURHANUDDIN (Universitas Riau, 2017)
Supervision by principal is important undertaken for quality controlling,professional developing and job motivation increasing so it influences teachers’ performance togain education quality. Supervision result is expected that education will be constant and relevantto the needs of society, the world of work or further education. The purpose of this study wasto clarify the effect of supervision by principal on job motivation and teachers’ performance atSMP Pesisir District of Siak Regency. The population of study was consist of 120 teachers byusing proportional random sampling technique so the total sample of research was 92 respondent.Data collection technique used was questionnaire of Linkert Scale for each of variableinvestigation. The data were analyzed by using Path Analysis. The result of study showed that: (1) supervision by principal significant effect directly on teachers’ performance at SMP PesisirDistrict of Siak Regency with significance level of 0.002. (2) Supervision by principal significanteffect directly on teachers’ performance at SMP Pesisir District of Siak Regency withsignificance level of 0.000. (3) Job motivation significant effect directly on teachers’ performanceat SMP Pesisir District of Siak Regency with significance level of 0.015. (4) Supervision byprincipal significant effect indirectly on teachers’ performance through job motivation at SMPPesisir District of Siak Regency with significance level of 0.000 and 0.015. By using PathAnalysis calculation with significance level of 5 %, it was gained the following structure : (1)X2 = 0.312 X1 + 0.950 õ1. Based on sub structure 1 was obtained 9.7% the contribution ofsupervision by principal on job motivation and 90.3% was influenced by another factors of outof model. (2) Y = 0.372 X1 + 0.239 X2 + 0.8660 õ2. Based on sub structure 2 was obtained25% the contribution of supervision by principal and job motivation on teachers’ perfomanceand 75% was influenced by another factors of out of model. So it can be concluded thatSupervision by principal effect 9.7% directly on job motivation. Supervision by principal effect13.8% and job motivation 5.7% directly on teachers’ perfomance at SMP Pesisir District ofSiak Regency. Supervision by principal effect indirectly 0.5% on teachers’ performance throughjob motivation at SMP Pesisir District of Siak Regency so that the total effect was 9.8 %. Thusthe research hypothesis was formulated tested and acceptable.